DINAMIKA TEMPORAL TEKANAN PENDUDUK TERHADAP LAHAN DAS JLANTAH HULU KABUPATEN KARANGANYAR TAHUN 2006 – 2016 (Suplemen Kurikulum 2013 SMA Kelas XI Kompetensi Dasar Menganalisis Bentuk-bentuk Kearifan Lokal Dalam Pemanfaatan Sumber Daya Alam Bidang Pertanian, Pertambangan, Industri, dan Pariwisata) - Riyan Astiti Pradikka; Wakino .; Rahning Utomowati (GeoEco, 2017)
Temporal Dynamic of Population Pressure on Land in the Upper Jlantah Watreshed (Supplements of Curriculum 2013 in High School Class XI Basic Competence Analyzing Forms of Local Wisdom in Natural Resources Utilization Field Agriculture, Mining, Industry, and Tourism). Graduate thesis. Supervisor I: Wakino, II: Rahning Utomowati, S.Si, M.Sc,. Teacher Training and Education. Sebelas Maret University Surakarta. The goals of this study are to determine: (1) population pressure of land in the Upper Jlantah watershed in 2006, (2) population pressure of land in the Upper Jlantah watershed in 2016, (3) dynamic of temporal change the population pressure of land in the Upper Jlantah watershed during 2006 – 2016, (4) the implementation in Basic Competence Analyzing Forms of Local Wisdom in Utilization of Natural Resources in Agriculture, Mining, Industry and Tourism in class X Social Science Program.This research is a descriptive qualitative research with spatial approach. Technique of data collecting is done by interview, observation, and documentation study. Processing and data analysis using Geographic Information System (GIS). Sampling technique used in this research is population sampling technique and purposive sampling. The population sample aims to obtain data on the area of crop harvest as a basis for determining population pressure on the land in the Upper Jlantah watershed. The result of this research reveals : (1) The high value of population pressure on land in the Upper Jlantah watershed in 2006 was 4.78, and the lowest was 0.60. High population pressure is found in Tawangmangu Village, Kalisoro, Blumbang, Gondosuli and Beruk. Low population pressure is found in the villages of Wonorejo, Tlobo, and Karangsari, (2. The high value of population pressure on land in the Upper Jlantah River in 2016 is the highest at 1.95, and the lowest is 0.31. High population pressure is found in Tawangmangu, Kalisoro, Blumbang, Gondosuli and Beruk. Low population pressure is found in the villages of Wonorejo, Tlobo, and Karangsari, (3). During the period of 2006 - 2016, population pressure on land in upstream Jlantah watershed tended to decrease, but if based on the standard (TP value 1), for Tawangmangu, Kalisoro, Blumbang, Gondosuli and Beruk, Areas belonging to the lower classes are Wonorejo, Tlobo, and Karangsari, (4). As an implementation in the field of education, this research in geography learning can be used as a material for learning geography of SMA XI IPS Semester 1 Curriculum 2013 on basic competence to analyze the forms of local wisdom in the utilization of natural resources in agriculture, mining, industry and tourism. Keywords: temporal dynamic, Population Pressure on Land, upper watershed, implementationof bacis competence